Animal Magnetism: Ecocritical New Materialism for the Anthropocene - Rossello, Diego (Rivista Italiana di Filosofia Politica, 2025)
The paper explores animal magnetism for ecocriticism in the Anthropocene. Animal magnetism rose in the years prior to the French Revolution, when mesmerism became influential among Jacobins, but it has been recuperated by contemporary thinkers for whom ecocriticism intersects with new materialism, feminist theory, animal studies, and political theology. Then and now, animal magnetism’s relevance for ecocriticism lies in its radical egalitarianism across species; in an enchanted worldview attentive to fluxes of sympathy; and in its emphasis on a harmonious relation with nature.